Preserving the Sixties Britain and the ‘Decade of Protest’ - Harris, Trevor.; Harris, Trevor.; Castro, Monia O’Brien.; Castro, Monia O’Brien. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Re-examining the long-held belief that the Sixties in Britain were dominated mainly by 'youth' and 'protest', the authors in the collection argue that innovation was everywhere shadowed by conservatism. A decade fascinated by itself and, especially, by the future, it also was tormented by self-doubt and accompanied by a fear of losing the past.